2013
DOI: 10.1016/j.clineuro.2013.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vascular disease as remote ischemic preconditioning, for acute stroke

Abstract: Obectives Remote ischemic preconditioning (RIPC) is a powerful endogenous mechanism whereby a brief period of ischemia is capable of protecting remote tissues from subsequent ischemic insult. While this phenomenon has been extensively studied in the heart and brain in animal models, little work has been done to explore the effects of RIPC in human patients with acute cerebral ischemia. This study investigates whether chronic peripheral hypoperfusion, in the form of pre-existing arterial peripheral vascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
0
24
1
2
Order By: Relevance
“…This was supported with measurement and analysis of creatine kinase, infarct size on imaging, development of malignant arrhythmia, mortality and neurologic disability (Abete et al, 1997; Castillo et al, 2003; Lorgis et al, 2012; Moncayo et al, 2000; Wegener et al, 2004). Also, patients with peripheral vascular disease (PVD) and sleep apnea (through repetitive hypoxic crises) may have experienced naturally occurring ischemic preconditioning (Connolly et al, 2013; Koch et al, 2007). PVD patients had better functional outcomes and smaller stroke volumes according to an observational study.…”
Section: Clinical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported with measurement and analysis of creatine kinase, infarct size on imaging, development of malignant arrhythmia, mortality and neurologic disability (Abete et al, 1997; Castillo et al, 2003; Lorgis et al, 2012; Moncayo et al, 2000; Wegener et al, 2004). Also, patients with peripheral vascular disease (PVD) and sleep apnea (through repetitive hypoxic crises) may have experienced naturally occurring ischemic preconditioning (Connolly et al, 2013; Koch et al, 2007). PVD patients had better functional outcomes and smaller stroke volumes according to an observational study.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…PVD patients had better functional outcomes and smaller stroke volumes according to an observational study. Cerebroprotection was felt to be the result of chronic limb ischemia (Connolly et al, 2013). The mechanisms involved in ischemic conditioning have been derived primarily from IPrC research.…”
Section: Clinical Considerationsmentioning
confidence: 99%
“…В 2013 г. M. Connolly и соавт. опубликовали результаты своих наблюдений у пациентов с ишемическим инсультом (ИИ) [17]. Больных разделили на 2 группы: 1) пациенты с заболеванием периферических сосудов (ЗПС); 2) больные без поражения периферических сосудов.…”
Section: контактная информацияunclassified
“…Выяснилось, что инсульт протекает легче у пациентов с ЗПС, а частота летальных исходов у них в 2 раза ниже, чем у больных без поражения перифериче-ских артерий. Авторы публикации полагают [17], что ЗПС явля-ется аналогом ДИП у человека и рассматривают полученные дан-ные как доказательство существования нейропротекторного дей-ствия ДП у человека. В 2014 г. опубликованы результаты много-центрового исследования, включавшего 335 больных с острым нарушением мозгового кровообращения (преходящее нарушение мозгового кровообращения -58, ИИ -240, ГИ -37) [18].…”
Section: контактная информацияunclassified
“…Examples of such potential preconditioning include the effects of surgical incisions 25 and underlying vascular disease. Recently, Connolly et al 29 found that patients with pre-existing arterial peripheral vascular disease may be protected from acute ischemic stroke. This might be a result of limb hypoperfusion having similar effects to RIPC.…”
mentioning
confidence: 99%